The Oral Mucosa Status and the Correlation between the Functional Parameters and the Level of Nitric Oxide Metabolites in Saliva among Patients with GERD - G. I. Lukina; A. V. Ivannikova; M. Y. Abramova; E. M. Kuzmina; A. V. Lukin; A. V. Alimova; A. B. Slabkovskaya (International Journal of Dentistry)
The study involved 91 patients (48 women and 43 men), aged from 18 to 70 years with GERD. All patients underwent the clinical dental examination according to a single scheme including general clinical manifestations (nausea, single vomiting, belching, heartburn, pain in the epigastrium and around the navel, and poor appetite) and dental manifestations of GERD. The objective assessment of the dental status of the examined patients included the measurement of the functional parameters of the mixed saliva, buffer capacity (BC) of saliva, and the detection of the nitric oxide metabolites (NOx) content in saliva from the right parotid salivary gland (“SRPSG”) and in blood serum using the indirect method based on the determination of the stable metabolites: nitrates and nitrites using the Griess reaction. It was established that salivation rate among patients with GERD with the prevailing of ACR and SACR was at the lower limit of normal values (0.32 + 0.19 ml/min), and the salivation rate among patients with the prevailing of SALCR was low (0.10 + 0.04 ml/min). The BC of saliva among patients with the prevailing of ACR and SACR was high (9.07 + 1.23 mmol eq/l and 9.40 + 1.71 mmol eq/l, respectively) and was reduced among patients with the prevailing of SALCR (7.63 + 0.18 mmol eq/l). The NOx level in SRPSG among patients with GERD was increased (especially in Group 3 (20.93 + 11.23 umol/l)). The direct correlation between the indicators of sialometry, the level of the BC of saliva, and the NOx level in SRPSG were established during the study.